A binder-free paper electrode with high performance for NaBH4 oxidation. (24th November 2017) - Zhang, Dongming; Wang, Bin; Yang, Xueying; Zhang, Junjun; Liu, Youzhi; Wang, Guiling
Abstract : In this study, a piece of filter paper with good flexibility and hygroscopicity was used to support catalysts after a pencil drawing process. Abstract : In this study, a piece of filter paper with good flexibility and hygroscopicity was used to support catalysts after a pencil drawing process. A layer of thin Ni film was deposited on the surface of the conductive graphite layer using an electrochemical method at a negative potential. Pd nanoparticles with high electrocatalytic activity for NaBH4 oxidation were introduced by immersing the Ni film-graphite-filter paper (NGF) in PdCl2 solution to obtain a Pd-NGF (PNGF) electrode. The morphology and phase structure of PNGF were characterized using scanning electron microscopy (SEM) equipped with an energy dispersive X-ray spectrometer (EDS), transmission electron microscopy (TEM) and an X-ray diffractometer (XRD). The PNGF electrode was used as the anode in direct borohydride fuel cells (DBFCs), and the electrochemical properties for NaBH4 oxidation were determined by cyclic voltammetry (CV), chronoamperometry (CA) and electrochemical impedance spectroscopy (EIS). The oxidation current density reaches 550 mA cm −2 at −0.4 V when the electrolyte contains 2 mol dm −3 NaOH and 0.10 mol dm −3 NaBH4 .